The Tajwidul Method in Qur'anic Learning in the Digital Era: Detecting Qur'anic Pronunciation Errors Through TikTok Live - Bahana Kalamurrahman; Wawan Hermawan; Achmad Faqihuddin (Bulletin of Pedagogical Research, 2025)
Learning the pronunciation of letters in reading the Qur'an has a very important role in maintaining the authenticity of the meaning of the verses of the Qur'an. Mistakes in pronouncing the hijaiyah letters can significantly change the meaning of the verses, which has an impact on the understanding and practice of Islamic teachings. Along with the development of digital technology, the use of social media, such as TikTok, offers great potential to improve tajwid learning in a more interactive and accessible way to a wider audience. This study aims to examine the application of the tajwidul method in learning the Qur'an through the TikTok Live platform, with a focus on detecting and correcting errors in pronouncing hijaiyah letters in real time. The research method used is qualitative with a case study design, which includes an analysis of 13 TikTok videos of Ustadz Gifari Putra and direct observation during the TikTok Live session. The results of the study show that direct interaction through TikTok Live is effective in improving students' understanding of correct pronunciation, with the help of clear visualization of mouth and tongue movements. However, technical constraints such as signal quality and limited time to provide personal attention remain challenges in implementing this method. This study contributes to the development of tajwid learning in the digital era, and offers recommendations to improve the quality of tajwid teaching through social media, especially TikTok, by optimizing interactive and visualization features.